Proteostasis collapse in rat’s lung tissue as one of the effects of European adder (Vipera berus subsp. berus and Vipera berus subsp. nikolskii) envenomation - Shchypanskyi Serhii; Maievskyi Oleksandr; Lasavutz Vladyslav; Sokurenko Liudmyla; Raksha Nataliia; Halenova Tetiana; Vovk Tetiana; Savchuk Olexii (Current Issues in Pharmacy and Medical Sciences, 2024)
Snakebites and their consequences are a growing concern around the globe. The mixture of enzymes, present in snake venom is a great challenge for a snakebite victim’s body. European adder (Vipera berus) is considered as not very harmful snake due to the mild clinical symptoms of envenomation and rare cases of cardiovascular or pulmonary failure. Nevertheless, at the molecular level, many details of V. berus bite (including proteostasis instability) remain unclear. This work was aimed to determine the effect of Eastern Europe typical adder species Vipera berus berus and Vipera berus nikolskii envenomation on the protein homeostasis of rat’s lung tissue. The decrease in total protein concentration, significant redistribution of main protein fractions (including proteolytically active), rise in middle-mass molecules and low molecular weight peptide concentration have been observed during V. b. berus and V. b. nikolskii envenomation, strongly indicating the proteostasis collapse and endogenous intoxication in lung tissue as an effect of European adder snakebite. Moreover, according to the results of experiments, the effect of V. b. nikolskii venom is more harmful to lung tissue protein homeostasis, comparing to V. b. berus, suggesting that the former may represent a greater danger to people. The results of this study may find applications in antivenom development and could be taken into consideration for proper snakebite treatment selection in order to avoid proteome complications in patients.